Draft Annual Plan 2000-2001 Volume-I Government of Manipur - Planning Commission (Planning Commission, 2000)
Manipur continues to be one of the most backward States in the country. As per the Index of Relative Development of Infrastructure for 1991-92 prepared by the Centre for Monitoring of Indian Economy, Manipur occupies a low place in the list. In terms of infrastructural development, the State lags behind the rest of the country by 21%.
Planning Department Government of Manipur